Overcorrected lower limb axis as an outcome of unicompartmental knee arthroplasty - Nikolay N. Kornilov; Dmitriy V. Chugaev; Pavel P. Ivanov; Magomed Sh. Magomedov; Taras A. Kulyaba; Alexey S. Phil (Гений oртопедии)
Introduction Unicompartmental knee arthroplasty (UKA) is an effective surgical procedure used in patients with gonarthrosis with a part of the knee being severely affected. Insufficient or excessive correction of the lower limb axis can cause a poor outcome of partial arthroplasty. The objective was to evaluate ways that would help prevent insufficient or excessive correction of the lower limb axis with UKA and demonstrate techniques preventing and solving the surgical problem using a clinical example. Material and methods A patient presented with valgus deformity at the knee level, knee pain and inability to walk without support was seen at the Vreden National Medical Research Centre for Traumatology and Orthopedics. The patient underwent UKA three years ago. The radiographs showed sparing resections of the femur and tibia, the working surface of the polyethylene liner/tibial implant component being 5 mm proximally to the articular surface of the lateral condyle of the tibia. Results and discussion The limb axis was corrected by 6° during revision arthroplasty. The patient had no limping at one year and the result of the operation was rated as excellent measuring 45 OKS scores. The authors reviewed prerequisites of the complication in question and ways to prevent it. Iatrogenic causes primarily associated with surgical technique are reviewed. Conclusion Inadequate mechanical alignment is characterized by a heterogeneous identity in UKA and can be caused by ineffective preoperative planning and specific anatomy of the patient, intraopereative technical failures.